Advanced services and differentiation advantage: an empirical investigation. Issue 9 (3rd July 2020) - Sousa, Rui; da Silveira, Giovani J.C.
Abstract : Purpose: This study theoretically articulates and empirically validates a model of relationships between market complexity (competition intensity, heterogeneity and technological change), strategic focus on product and service differentiation, ADS offerings and differentiation advantage. Design/methodology/approach: The authors develop and test hypotheses through structural equation modeling based on data from the Sixth International Manufacturing Strategy Survey (IMSS-VI), involving 931 manufacturers from 22 countries. Findings: The results indicate that (1) market complexity has a positive impact on strategic focus on product and service differentiation; (2) focus on product and service differentiation, but not market complexity, has a positive impact on the extent to which business units offer ADS to their customers; (3) ADS have a positive impact on service differentiation advantage, but no influence on product differentiation advantage. Practical implications: Managers should incorporate decisions related to ADS provision as part of their manufacturing strategy formulation processes to align markets, strategic focus on product and service differentiation, and ADS provision. ADS seem an appropriate lever for market differentiation, because they appear not only to support service differentiation advantage, but also to be consistent with strategic focus on product differentiation. Originality/value: The study provides novel insights and large-scale empirical evidence on the influence of the market environment on the offering of ADS, as well as on how relationships between the product and service activity in the manufacturing organization may affect differentiation advantage.